The Relationship Between Interpersonal Skills and Literacy Culture with Teachers' Teaching Creativity in Public Elementary Schools in Makassar City - Muhammad Saeful; Ulfayani Hakim; Heri Hermawan (Journal of Development Research, 2024)
Creativity in teaching in the era of the industrial revolution 4.0 should be prioritized and optimally developed by a teacher today. The need for creativity in education, especially in teacher teaching techniques, is now felt to be a need for students, especially at the elementary school level. In presenting effective learning, teachers should have various skills, one of which is good interpersonal skills, so that effective learning will be created and carried out properly. On the other hand, the awareness of familiarizing literacy culture among teachers is one of the efforts to develop the productivity of a teacher in designing various lessons for students. In connection with this, a study was conducted which aims to review and find out: 1) the description of interpersonal skills, literacy culture, and teaching creativity of public elementary school teachers in Makassar City, 2) the relationship between interpersonal skills and literacy culture together with teaching creativity of public elementary school teachers in Makassar City, 3) the relationship between interpersonal skills and literacy culture partially with teaching creativity of public elementary school teachers in Makassar City.